Preliminary study on hyperspectral remote sensing of Qiandao Lake chlorophyll-a concentration - LIU Ying; WANG Ke; ZHOU Bin; XU Hong-wei; SHEN Zhang-quan (浙江大学学报. 农业与生命科学版)
Qiandao Lake is the biggest freshwater reservoir of Zhejiang Province. This study was conducted to establish correlations between reflectance and concentration of chlorophyll-a in Qiandao Lake. Reflectance spectra was measured on July 4, 2001 using Fieldspec radiometer. Extensive water quality sampling was carried out simultaneously with the spectral data collection. The features of the spectral reflectance of the lake water were discussed. The reflectance ratio of R701nm/R516nm was found to be significantly correlated with the concentration of chlorophyll-a. It was also found that the correlation between the concentration of chlorophyll-a and the reflectance ratio of red/blue band of IKONOS data was also high, so it is possible to monitor the water quality of Qiandao Lake using remote sensing data.